Handbook of forensic science - Fraser, Jim; Williams, Robin (Willan, 2009)
This handbook provides an authoritative map of the landscape of forensic science within the criminal justice system of the UK. It sets out the features of the subject, covering the disciplinary, technological, organizational and legislative resources that are brought together to make up contemporary forensic science practice